PERANCANGAN PESAN KOMUNIKASI KOMUNITAS HONG DALAM SOSIALISASI MAINAN DAN PERMAINAN TRADISIONAL SUNDA - Susanti, Santi; Nurtania, Yuni (Universitas Semarang, 2017)
Hong Community as study center of traditional toys in West Java was formed with the intention of preserving traditional toys and folk games in West Java. As part of the effort to introduce traditional toys, especially to children. This study aims to identify and analyze the process of designing communication messages in the community of Hong in connection to the effort of socializing folk games and traditional toys in West Java. This study evolved five groups of communication target of Hong Community: the public, the government, fellow community members, working partner, the sponsors. The designing process of community communication that Hong Community uses to address its target audience, can be divided into 5 (five) stages as follows: (1) to define communication goals, (2) to identify the target audience, (3) to define the management system of communication event, (4) preparation of facility and infrastructure, and (5) message delivery.